Mapping and the spatial analysis of disability in the Khuzestan Province, Iran - Razavian, Mohammad Taghi; Fanni, Zohre; Tavakolinia, Jamileh; Mohammadi, Alireza; Pishgar, Elahe (Indonesian Journal of Disability Studies, 2019)
This study aims to mapping and spatial analysing of disability in the Khuzestan Province, Iran by using Geographic Information System. A total of 82, 674 disabled people information were included in the study. The 40 informational fields have been classified into 11 main categories. The Geographically Weighted Regression (GWR) technique were used for mapping and discovering the relationships. The results show that, 68.87% of the disabled people were urban residents. The disability rate of cities ranges from 10.54 to 43.05. As many as 63.43% of the disabled suffered from severe and extremely severe disabilities. About 60.59% of disabled were males 65.17% were married. In terms of educational level, as many as 87.61% of them had educational levels lower than junior high school. In terms of occupational status, about 74.24% of them were unemployed. There was a positive relationship between poverty and disability rate in 70.37% of the counties. Moreover, there was a positive relationship between population and disability ratio. In terms of disability variables, a significant difference was observed between different counties. The output of GWR method indicates that there was a positive and significant relationship between population and poverty level with disability ratio (Std. Dev. ‰¥ 0.05). However, the severity of this relationship varies in different counties.